Political Ideology and Endogenous Trade Policy: An Empirical Investigation - Dutt, Pushan; Mitra, Devashish (The Review of Economics and Statistics, 2005)
In this paper, we investigate empirically how government ideology affects trade policy. The prediction of a partisan, ideology-based model (within a two-sector, two-factor Heckscher-Ohlin framework) is that left-wing governments will adopt more protectionist trade policies in capital-rich countries, but adopt more pro-trade policies in labor-rich countries, than right-wing ones. The data strongly support this prediction in a very robust fashion. There is some evidence that this relationship may hold better in democracies than in dictatorships, though the magnitude of the partisan effect seems stronger in dictatorships.